Aplikasi Multimedia Untuk Pembelajaran Berbasis Simulasi Heuristik Dengan Konektifitas Scorm - Putrodjojo, Gunawan (Prosiding SNATIKA Vol 01 (2011), 2011)
Multimedia application has an advantage because it is more interesting and has many variations than simple GUI application. Multimedia application for learning has the purpose to make learners able to understand the material given and mapping the mind-set that is expected. Multimedia Application based-Simulation Heuristic for Extraction Maceration Module with SCORM Connectivity is developed using SDLC Throwaway Prototyping. The material from this application is developed using ISD ADDIE model. To communicate with Learning Management System (LMS), this application created based on SCORM 1.2 standard for online learning content. Implementation of this application used to support the learning process of General and Organic Chemistry in Universitas Pelita Harapan (UPH) and uploaded in LMS MOODLE UPH. This application is made so that learners are able to deduce and discover the relation between four factors under extraction with total yield obtained by conducting the experiments of extraction simulation. From the experiment of extraction simulation that have been conducted learners can evaluate and get the highest yield from 81 alternatives that exist but learners must consider the effectiveness from the factors that used and if these factors are worth with yield obtained too. Keywords: Multimedia, multimedia application, Extraction Maceration Module.